Plant family identity distinguishes patterns of carbon and nitrogen stable isotope abundance and nitrogen concentration in mycoheterotrophic plants associated with ectomycorrhizal fungi - Hynson, Nicole A. (Ann Bot, 2016)
Background and Aims Mycoheterotrophy entails plants meeting all or a portion of their carbon (C) demands via symbiotic interactions with root-inhabiting mycorrhizal fungi. Ecophysiological traits of mycoheterotrophs, such as their C stable isotope abundances, strongly correlate with the degree of species’ dependency on fungal C gains relative to C gains via photosynthesis. Less explored is the relationship between plant evolutionary history and mycoheterotrophic plant ecophysiology. We hypothesized that the C and nitrogen (N) stable isotope compositions, and N concentrations of fully and partially mycoheterotrophic species differentiate them from autotrophs, and that plant family identity would be an additional and significant explanatory factor for differences in these traits among species. We focused on mycoheterotrophic species that associate with ectomycorrhizal fungi from plant families Ericaceae and Orchidaceae. Methods Published and unpublished data were compiled on the N concentrations, C and N stable isotope abundances (δ(13)C and δ(15)N) of fully (n = 18) and partially (n = 22) mycoheterotrophic species from each plant family as well as corresponding autotrophic reference species (n = 156). These data were used to calculate site-independent C and N stable isotope enrichment factors (ε). Then we tested for differences in N concentration, (13)C and (15)N enrichment among plant families and trophic strategies. Key Results We found that in addition to differentiating partially and fully mycoheterotrophic species from each other and from autotrophs, C and N stable isotope enrichment also differentiates plant species based on familial identity. Differences in N concentrations clustered at the plant family level rather than the degree of dependency on mycoheterotrophy. Conclusions We posit that differences in stable isotope composition and N concentrations are related to plant family-specific physiological interactions with fungi and their environments.